Camera trapping of wildlife in the newly established Baleh National Park, Sarawak - Cheok, Melynda Ka Yi (2021)
The persistence of biodiversity in the Bornean rainforest depends on its ability to adapt to anthropogenic exploitation. The remaining forests in Sarawak are fragmented and isolated and their ability to support large sized mammals is of great concern. In view of this, camera trapping survey was conducted in the recently gazetted Baleh National Park to record the richness, activity pattern and distribution of medium-to-large sized mammals. A total of 15 infrared camera traps were set within the park. We identified at least 27 species of mammals, 12 birds and two reptiles. From the total mammalian species detected, four were listed as “totally protected” and 15 as “protected” under the Sarawak Wild Life Protection Ordinance 1998. Additionally, under the IUCN 2018 Red List criteria, one species was identified as “critically endangered” (Manis javanica), one as “endangered” (Catopuma badia), seven as “vulnerable” and four as “near threatened”. This study had identified the occurrence and distribution of some rare, endangered and threatened species. The presence of these species can be used to identify core conservation sites within Baleh National Park.